Strategy for Kleder Competency Improvement in The Camara Nusantara Cattle Ship - Fuah, A. M.; Zulhijariyanto; Cyrilla, L.; Triyonggo, Y.; Assegaf, Z. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Camara Nusantara ship was provided for livestock transportation especially cattle, to help increasingefficiency and decrease weight losses in the supply chain process. There were, however, such poor cattleperformance was still found on the arrival port, which was claimed as related to the poor managementand less competence of working personnel on board, one of those was kleder. This study was aimed atanalyzing the strategy for increasing Human Resource competency in the Camara Nusantara LivestockShip. Method used in this study was observations on target location, documentation, literature review,and depth interviews with target respondents in the respective locations, qualitative analysis approachwas applied for data analysis. Analytical Hierarchy Process (AHP) with five levels were used to analyzedata obtained from the study. The results indicate that the main strategies for increasing the competencyof human resource in the Camara Nusantara Livestock Ship was started with development of competencystandardization with a weight of 0.361. Development of competency standards for kleder is required toprovide a guidelines for improving kleder’s skills and knowledge in managing and handling livestockat Camara Nusantara Livestock Ship. It can be concluded that to optimize kleder competency who areworking at Camara Nusantara Cattle Ship may help to maintain cattle performance during the sea tolltransportation. Therefore, developing a national job competency standard, so called SKKNI (StandarKompetensi Kerja Nasional Indonesia) is needed as guidance to formulate relevant training programsfor human resource development.